PENERAPAN MODEL PEMBELAJARAN LANGSUNG MENGGUNAKAN GARIS BILANGAN UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DI KELAS VII SMP NEGERI 3 BANAWA - Diana, Diana (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The purpose of this study was to obtain a description of the application of direct instruction models using the number line that can enhance students' ability in solving addition and subtraction of integers in class VII 3 Banawa Junior High School . Kind of research is action research . This research design refers to the design of the study Kemmis and Mc . Taggart namely planning, action , observation and reflection . The results showed that the application of direct instructionÂ  models using the number line that can enhance students' ability in solving addition and subtraction of integers follow the phases namely : an introduction / introduction , presentation , guided practice , and independent practice .